Examining the attainment of learning outcome for spoken production in a CEFR-mapped English Course at CELPAD, IIUM: A case study - Kassim, Rosnani; Anuar, Siti Zubaidah; Abdullah, Liza (CELPAD Research Unit, CELPAD, International Islamic University Malaysia, 2023)
The efforts in bringing the English proficiency level of Malaysian students to international standard have led to the advent of the English Language Roadmap 2015-2025. At tertiary level, the language proficiency targeted among graduates is CEFR level C1. As all Higher Learning Institutions (HILs) are partaking in this national agenda, the International Islamic University Malaysia (IIUM) is committed in doing so and has worked towards fulfilling it by mapping the curriculum and assessments of its English Language courses to CEFR. One of them is English for Academic Writing, a university required courses. Apart from its emphasis on academic writing, this course also incorporates oral presentation. After implementing the curriculum for 2 academic years (2020/2021 & 2021/2022), it is imperative to analyse whether the Learning Outcome (LO) for speaking skills: Can give a clear, well-structured presentation of a complex subject by expanding and supporting points of view at some length with supporting points, reasons and relevant examples, which is mapped to CEFR C1 has been successfully attained. Hence, this case study was conducted to analyse students’ performance in spoken production of 3 students. The oral presentations were recorded, transcribed and then analysed using qualitative data analysis method. The research instrument used was a marking scheme with descriptors mapped to CEFR Can-do statements for level C1 for addressing audience (giving presentation). The analysis revealed that the students demonstrated the speaking ability of CEFR C1 based on the topic, range, accuracy, fluency, coherence and phonology. This study concluded that for the 3 students, the learning outcome has been attained and they would graduate with CEFR level C1 in speaking skills.